Psychological burnout among some primary school teachers in Madinah in light of distance education during (COVID-19) - Al-Shamani, Mariam Rashid; Al-hadidi, Saud Abdulaziz (Journal of Educational and Psychological Sciences, 2022)
The current study aimed to identify the level of psychological burnout among primary school teachers in Medina in the light of distance education during the Corona pandemic (COVID-19), and to identify the differences in the level of psychological burnout according to the variables (years of service and marital status), and the researcher used the descriptive approach, and the tool was represented in the measure of psychological combustion of teachers in its modified form by the researcher and consists of (23) phrases distributed over (4) dimensions, applied to a random sample of (306) teachers, and the results of the study showed that The general arithmetic average of the level of burnout among primary school teachers in Medina was (2.50 out of 5) with a combustion estimate (weak) and (50.0%), and at the dimensional level, it was first solved by "job dissatisfaction" by (2.72), then "occupational pressure" by (2.61), third "negative trend towards students" by (2.38), and finally, the decrease in the level of administrative support by (2.29). All of them are estimated to be (weak) combustion and the absence of statistically significant differences in the level of psychological burnout among primary school teachers in Medina in light of distance education during the Corona pandemic (COVID-19) according to the two variables of the study, and based on the results the researcher recommended holding more training courses for male and female teachers, and adopting the method of distance education during bad weather, such as: extreme cold, rain, instead of suspending study.
Keywords: Psychological burnout; Primary school; Madinah; Distance education; COVID-19